The Role of Cyclooxygenase in Multiplication and Reactivation of HSV-1 in Vestibular Ganglion Neurons - Yuehong Liu; Shufeng Li; Zhengmin Wang (The Scientific World Journal)
Reactivation of latent herpes simplex type 1 (HSV-1) and nerve inflammation have been shown to be involved in vertigo-related vestibular pathogenesis. Treatments of such diseases have been less than perfect. Nonsteroidal anti-inflammatory drugs (NSAIDs) have been reported to suppress reactivation of HSV-1 in trigeminal ganglions. However, whether this drug can affect reactivation of HSV-1 in vestibular ganglions is unclear. Due to the difficulties of constructing in vivo animal models, in this study, we developed a vestibular ganglion culture system, in which vestibular neurons were latently or lytically infected with HSV-1. Indomethacin and celecoxib were selected to measure their effects on HSV-1. Trichostatin A was used to reactivate HSV-1 in latently infected neurons. Cycloxygenase-2, which is the target of NSAIDs, was induced by HSV-1 in the lytically infected cultures, with an increase of 14-fold. Although it appeared that indomethacin and celecoxib showed limited but concentration-dependent inhibition effects on viral production under our condition, indomethacin decreased reactivation rate of HSV-1 by about 20%. Though more in vitro or in vivo studies are needed to confirm the effects of the drugs, our study may provide a potential way to investigate the mechanism of HSV-related vestibular pathogenesis as well as new treatments of vertigo-related diseases.